KONTRIBUSI SHAYKH MAHFÛZ AL-TARMASÎ DALAM PERKEMBANGAN ILMU HADIS DI NUSANTARA - Fauzan, Ahmad (UIN Sunan Kalijaga Yogyakarta, 2018)
This article examines the intellectual figures of the hadith in Nusantara whose works have worldwide with a background of inspiration from the phenomenon of Nusantara’s hadith figures that are spelled out so much, such as al-Raniri, Yasin al-Fadani, Hasyim Asy’ari, Maḥfûẓ al-Tarmasî, and so forth. This paper specifically examines one of the figures of the Ulamâ’ Nusantara, namely Maḥfûẓ al-Tarmasî, both in terms of biography, his contribution in the fields of hadith, qirâ’ah, and sanad. The method used in this paper is a content data analysis using literature studies (library research). The expected result of this paper is that the breadth of al-Tarmasî’s scientific knowledge is not only limited to the discipline of hadith or its knowledge, but also other disciplines such as qirâ’ah, fiqh and so forth. In this study, it was concluded that al-Tarmasî had a major contribution to the spread of qirâ’ah in Nusantara. He became the main reference in terms of qirâ’ah. Likewise, in the field of Hadith, the sanad owned by al-Tarmasî is connected in a chain to its author, and on this basis, many Indonesian take the path of teacher training to al-Tarmasî.Keyword: al-Tarmasi, Hadith, Nusantara